Role of Social Media for Drug Safety Signal Detection - Sulakhiya, Kunjbihari; Kanchan, Sushim; Ansari, Haroon; Kisku, Anglina (Indian Journal of Pharmaceutical Education and Research, 2024)
Drug safety is an important factor considered during the drug discovery and development stages to develop safe and efficacious medicines for patients. Post-marketing surveillance is the commonly used method to obtain Adverse Drug Reaction (ADR) data of a marketed product through spontaneous reporting. In recent years, drug side effects are a major concern related to public health, increasing hospitalization and mortality rates. Social media has gained popularity in communicating and sharing every aspect of human life, including health-related information. The advantages of using social media to detect and report pharmacovigilance signals include the dissemination of data among healthcare professionals and stakeholders in a real-time and timely manner. The main objective of this review article is to explore the possible role of social media in the detection of a drug safety signal. It is observed from the extensive review that patients are seeking advice and getting information about health, disease, and medications from different social networks such as LinkedIn, Facebook, WhatsApp, Twitter, Pharmacovigilance Programme of India (PvPI) app, PubMed, MedHelp, PatientsLikeMe, etc It is concluded that social networks can be a useful tool for the detection of a drug safety signal. Thus, few limitations of traditional data sources or signal analysis suggested that these traditional signal analyses can be supplemented with data gathered from social media.
Keywords: Pharmacovigilance; Adverse Drug Reactions; Drug Safety; Signal Detection; Social; Media